Estimation tools for reducing the impact of sampling and nonresponse errors in dual‐frame RDD telephone surveys - Wolter, Kirk M.; Ganesh, N.; Copeland, Kennon R.; Singleton, James A.; Khare, Meena (Statistics in medicine, 2019)
We discuss alternative estimators of the population total given a dual‐frame random‐digit‐dial (RDD) telephone survey in which samples are selected from landline and cell phone sampling frames. The estimators are subject to sampling and nonsampling errors. To reduce sampling variability when an optimum balance of landline and cell phone samples is not feasible, we develop an application of shrinkage estimation. We demonstrate the implications for survey weighting of a differential nonresponse mechanism by telephone status. We illustrate these ideas using data from the National Immunization Survey‐Child, a large dual‐frame RDD telephone survey sponsored by the Centers for Disease Control and Prevention and conducted to measure the vaccination status of American children aged 19 to 35 months.